Targeting Mycobacterium tuberculosis Antigens to Dendritic Cells via the DC-Specific-ICAM3-Grabbing-Nonintegrin Receptor Induces Strong T-Helper 1 Immune Responses - Velasquez, Lis Noelia; Stüve, Philipp; Gentilini, Maria Virginia; Swallow, Maxine; Bartel, Judith; Lycke, Nils Yngve; Barkan, Daniel; Martina, Mariana; Lujan, Hugo D.; Kalay, Hakan; van Kooyk, Yvette; Sparwasser, Tim D.; et al. (Frontiers in Immunology, 2018)
Tuberculosis remains a major global health problem and efforts to develop a more effective vaccine have been unsuccessful so far. Targeting antigens (Ags) to dendritic cells (DCs) in vivo has emerged as a new promising vaccine strategy. In this approach, Ags are delivered directly to DCs via antibodies that bind to endocytic cell-surface receptors. Here, we explored DC-SIGN targeting as a potential vaccine against tuberculosis. For this, we made use of the hSIGN mouse model that expresses human DC-SIGN under the control of the murine CD11c promoter. We show that in vitro and in vivo delivery of anti-DC-SIGN antibodies conjugated to Ag85B and peptide 25 of Ag85B in combination with anti-CD40, the fungal cell wall component zymosan and the cholera toxin-derived fusion protein CTA1-DD, induce strong Ag-specific CD4+ T cell responses. Improved anti-mycobacterial immunity was accompanied by increased frequencies of Ag-specific IFN-γ+ IL-2+ TNF-α+ polyfunctional CD4+ T cells in vaccinated mice compared to controls. Taken together, in this study we provide the proof of concept that the human DC-SIGN receptor can be efficiently exploited for vaccine purposes to promote immunity against mycobacterial infections.